Osmotrophic glucose and leucine assimilation and its impact on EPA and DHA content in algae - Elina T. Peltomaa; Sami Taipale (PeerJ, 2020)
The uptake of dissolved organic compounds, that is, osmotrophy, has been shown to be an efficient nutritional strategy for algae. However, this mode of nutrition may affect the biochemical composition, for example, the fatty acid (FA) contents, of algal cells. This study focused on the osmotrophic assimilation of glucose and leucine by selected seven algal strains belonging to chlorophytes, chrysophytes, cryptophytes, dinoflagellates and euglenoids. Our laboratory experiments with stable isotope labeling showed that osmotrophy occurred in four of the selected seven strains. However, only three of these produced long chain omega-3 FAs eicosapentaenoic acid (EPA; 20:5ω3) and docosahexaenoic acid (DHA; 22:6ω3). High glucose content (5 mg L−1) affected negatively on the total FAs of Mallomonas kalinae and the total omega-3 FAs of Cryptomonas sp. Further, glucose assimilation explained 35% (negative effect) and leucine assimilation 48% (positive effect) of the variation of EPA, DHA and the FAs related to their synthesis in Cryptomonas sp. Moderate glucose concentration (2 mg L−1) was found to enhance the growth of Cryptomonas ozolinii, whereas low leucine (20 µg L−1) enhanced the growth of M. kalinae. However, no systematic effect of osmotrophy on growth rates was detected. Our study shows that osmotrophic assimilation of algae is species and compound specific, and that the effects of the assimilated compounds on algal metabolism also varies depending on the species.